Mixed features: evolution of the concept, past and current definitions, and future prospects. (7th March 2017) - Swann, Alan C.
Abstract : Mixed states address the relationships between episodes and the course of an illness, presenting significant clinical challenges. Recurrent affective disorders were described thousands of years ago as dimensional disturbances of the basic elements of behavior, combining the characteristics of what we would now consider manic and depressive episodes. It was recognized from the beginning that combinations of depressive and manic features are associated with a severe illness course, including increased suicide risk. Early descriptions of affective disorders formulated them as systemic illnesses, a concept supported by more recent data. Descriptions of affective disorders and their course, including mixed states, became more systematic during the 19th century. Structured criteria achieved importance with evidence that, in addition to early onset, frequent recurrence, and comorbid problems, mixed states had worse treatment outcomes than other episodes. In contrast to 2000 years of literature on recurrent affective episodes and mixed states, the unipolar–bipolar disorder distinction was formalized in the mid-20th century. Mixed-state criteria, initially developed for bipolar disorder, ranged from fully combined depression and mania to the DSM–5 criteria, no longer limited to bipolar disorder, of a primary depressive or manic episode with at least three symptoms of the other episode type. The challenges involved in understanding and identifying mixed states center largely on what drives them, including (1) their formulation as either categorical or dimensional constructs, (2) the specificity of their relationships to depressive or manic episodes, and (3) specificity for bipolar versus major depressive disorder. Their existence challenges the distinction between bipolar and major depressive disorders. The challenges involved in identifying the underlying physiological mechanisms go to the heart of these questions.